Pre-operative Anemia as a Risk Factor of Morbidity and Mortality in Valvular Surgeries: Preoperative Anemia and Valvular Surgeries - Abbas, Sardar Saud; Sajjad, Muhammad Wasim; Naeem, Hamid; Ul Islam, Mujahid; Khan, Imran; Sabir, Ahsan; Imran, Owais; Arshad, Umair; Shah, Syed Nauman; Afridi, Rimshah (Pakistan Journal of Health Sciences, 2024)
Pre-operative anemia can be a hindrance to speedy recovery and will increase blood transfusion intraoperative and post operatively. Objective: To find a correlation between preoperative anemia and the subsequent morbidity and mortality rates in patients undergoing valvular surgeries. Methods: A retrospective observational study, involving 493 valvular surgeries’ patients. All patients had the same anesthetic and surgical techniques. According to the WHO, anemia is a hemoglobin level < 13 g/dl for men and <12 g/dl for women. Clinical variables were compared using chi-square and independent t-test. Results: The patients received cardiac surgery for valvular heart disorders and had an average age of 42.2±14.1 years, with 60.9% being male. Most patients exhibited NYHA III (48.9%) and CCS III (36.5%) functional class symptoms. Highest comorbidity was hypertension (35.1%), followed by diabetes (14.4%) and dyslipidemia (6.5%). 43.2% were anemic and older than non-anemic individuals (P=0.02). Anemic people had a significantly greater incidence of HTN (P 0.02) and DM (P < 0.001). Both groups exhibited identical perfusion and cross-clamp periods (P=0.4 vs. P=0.3). Though not statistically significant (P=0.08), non-anemic patients needed more intraoperative blood or blood product transfusions. Patients with anemia have worse outcomes, including increased rates of in-hospital mortality (P=0.03), extended artificial breathing (P=0.04), and postoperative blood/product transfusion (P<0.001). 44.8% of anemic individuals needed RCC, 41.9% FFP, and 41.4% platelets. Conclusions: anemia is associated with the poorest post-operative results. There is conflicting information about the impact of preoperative anemia, particularly iron deficiency anemia, on valvular surgery.